Investigation on Simultaneous Effects of Shot Peen and Austenitizing Time and Temperature on Grain Size and Microstructure of Austenitic Manganese Steel (Hadfield) - Beheshti, M. (Institute of Physics Publishing, 2018)
Optimal conditions to increase life time of casting parts have been investigated by applying various cycles of heat treatment and shot peening on Hadfield steel surface. Metallographic and SEM microstructure examinations were used to determine the effects of shot peen, austenitizing time and temperature simultaneously. The results showed that with increasing austenitizing time and temperature of casting sample, carbides resolved in austenite phase and by further increase of austenitizing temperature and time, the austenite grain size becomes larger. Metallographic images illustrated that shot peening on Hadfield steel surface; Austenite - Martensite transformation has not occurred, but its matrix hardened through twining formation process. Â© Published under licence by IOP Publishing Ltd.